PERLINDUNGAN HUKUM BAGI PEMBELI CONDOTEL MELALUI PERJANJIAN PENGIKATAN JUAL BELI - Suwardi; Boediningsih, Widyawati (Faculty of Law, University of Dr. Soetomo, 2022)
Efforts to protect the law for buyers of condotel units as consumers from developers, the legal aspects of buying and selling transfers must be fully understood by buyers. In the process of buying and selling fixed objects such as land, houses, apartments or other properties, they are bound by an agreement. The Sale and Purchase Binding Agreement (PPJB) is made to carry out a temporary binding before the official Sale and Purchase Deed (AJB) is made before the Land Deed Making Officer (PPAT). Generally, the Sale and Purchase Binding Agreement (PPJB) is made privately for a certain reason, such as the payment of the price has not been paid off. With the Sale and Purchase Binding Agreement, there are still frequent losses suffered by the buyer. This study aims to determine the legal protection for condotel buyers through PPJB. The method used in this paper is normative juridical, which refers to the legislation and literature study.The results of this study, that the Sale and Purchase Binding Agreement has been prepared by the developer or legal representative as a standard agreement whose contents are not in accordance with the terms of the standard agreement. Prior to the signing of the Sale and Purchase Agreement, prospective buyers are usually given the opportunity to read and study the draft of the Sale and Purchase Binding Agreement with the guidance of an officer. Keywords: Legal Protection, Buyers, Condotel, PPJB.